Quintus Aurelius Symmachus and the Roman Religion - Tóth, Orsolya (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
Quintus Aurelius Symmachus, the renowned orator of Late Antiquity, took an active role in upholding the traditions of the ancient Roman religion. The present paper examines his relationship to religion and his priestly activities, mainly through his letters.